From bioprocess to market: Optimizing medium-chain carboxylate extraction for application readiness - Yiran Zhang; Aijie Wang; Yilu Sun; Xuening Zhang; Jianfeng Liu; Wen Wang; Cong Huang; Shaoping Fu; Honggang Deng; Yongping Shan; Jiadong Yu; Xufeng Yuan; et al. (Bioresource Technology, 2026)

Flavor formation and microbial community dynamics in Dong ethnic fermented Anyu - Fenghong Li; Kelang Kang; Qun Huang; Xin li; Shaoping Deng; Yingjuan Wei; Hui Yang; Meijuan Yu (Food Research International, 2025)

A cytokine receptor domeless restrains mud crab reovirus infection via JAK-STAT signaling pathway in mud crab (Scylla paramamosain) - Hengwei Deng; Yetong Ke; Shaoping Weng; Lei Hu; Wenfeng Zhang; Yujia Sun; Linwei Yang; Xuewen Wang; Mingyang Feng; Weiliang Guo; Zhihong Zhong; Dongdong Zhang; et al. (Fish & Shellfish Immunology, 2025)

Multigenerational effects of disperse blue 79 at environmentally relevant concentrations on zebrafish (Danio rerio) fecundity: An integrated approach - Chao Wang; Wen Gu; Shaoping Zhang; Li Li; Jian Kong; Hong Zhi; Juan Liu; Mengmeng Wang; Ke Miao; Qi Li; Jie Yu; Runming Wang; et al. (Journal of Hazardous Materials, 2024)

Environmental dispersal and host priority effect alternatively dominate intestinal microbiota succession of cultured shrimp along with host development - Dongwei Hou; Renjun Zhou; Zhixuan Deng; Shenzheng Zeng; Shaoping Weng; Jianguo He; Zhijian Huang (Marine Life Science & Technology, 2024)

Application of alkaline sludge based LDHs in Cd and Cu polluted wastewater remediation: Process and mechanism - Qingsheng Xu; Zhengbo Yue; Rui Deng; Xinquan Wang; Xiao He; Xin Chuai; Shaoping Wang; Jin Wang (Journal of Water Process Engineering, 2023)

Basigin binds bacteria and activates Dorsal signaling to promote antibacterial defense in Penaeus vannamei - Linwei Yang; Zi-ang Wang; Yushi Gan; Hongliang Zuo; Hengwei Deng; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

Hepatic metabolism-related effects of polysaccharides from red kidney bean and small black soybean on type 2 diabetes - Zhouya Bai; Xiaojun Huang; Guangjie Wu; Yujia Zhou; Xingchao Deng; Jingrui Yang; Junyi Yin; Shaoping Nie (Food Chemistry, 2023)

Production and characterization of monoclonal antibodies against mandarinfish ranavirus and first identification of pyloric caecum as the major target tissue - Wenfeng Zhang; Hengwei Deng; Yuting Fu; Weixuan Fu; Shaoping Weng; Jianguo He; Chuanfu Dong (Journal of Fish Diseases, 2023)
Mandarinfish ranavirus (MRV), also known as a variant of largemouth bass virus (LMBV), is an emerging pathogen in mandarinfish aquaculture. In this study, monoclonal antibodies (mAbs) against MRV were produced and characterized, and 7 mAbs were obtained through Western blotting screening and all 7 mAbs specifically recognized MRV/LMBV but not several piscine iridoviruses as ISKNV, GIV and TFV. By LC MS/MS analysis, the recognized viral proteins by seven mAbs were identified as MRV‐pORF47L, MRV‐pORF55R, MRV‐pORF57L, MRV‐pORF77L and MRV‐pORF78L, respectively, and all five viral proteins are late expression structural proteins by Western blotting. Based on mAb 1C4, immuno‐histochemistry and immuno‐histo‐fluorescence were performed to re‐assess the tissue tropism of MRV. The result showed that abundant reactive signals were observed in infected spleen, kidney as well as intestine and pyloric caecum. Real‐time quantitative PCR also demonstrated that spleen as well as pyloric caecum and intestines are the major target tissue upon MRV infection. In infected intestines and pyloric caecum, numerous enlarged, multinucleated cells with intracytoplasmic inclusions were identified as the target cells of MRV, suggesting that MRV serves as a digestive tract pathogen to mandarinfish, which may explain why acute infection of MRV can cause the typical clinicopathology featured by severe ascites.

Selenium Content and/or T-2 Toxin Contamination of Cereals, Soil, and Children’s Hair in Some Areas of Heilongjiang and Gansu Provinces, China - Liyan Sun; Silu Cui; Qing Deng; Hui Liu; Yanhong Cao; Shaoping Wang; Jun Yu (Biological Trace Element Research, 2019)

The ARF, AUX/IAA and GH3 gene families in citrus: genome-wide identification and expression analysis during fruitlet drop from abscission zone A - Rangjin Xie; Shaoping Pang; Yanyan Ma; Lie Deng; Shaolan He; Shilai Yi; Qiang Lv; Yongqiang Zheng (Molecular Genetics and Genomics, 2015)

Isolation and characterization of eight microsatellite loci of Glyptothorax laosensis in the Lancang river - Ju Jin; DengQiang Wang; MingDian Liu; ShuangYu Yin; HuaTang Deng; ShaoPing Liu (Conservation Genetics Resources, 2012)

Distribution of different taste buds and expression of α-gustducin in the barbells of yellow catfish (Pelteobagrus fulvidraco) - Genhua Zhang; Shaoping Deng; Haiyun Zhang; Hongtao Li; Leilei Li (Fish Physiology and Biochemistry, 2006)